Long-lasting benefit on multimodal treatment combining osimertinib and stereotaxic radiotherapy for metastatic non-small cell lung cancer with the EGFR exon 20 insertion 773-774 HVdelinsLM: a case report - Louvet, Aurélie; Honoré, Natasha; Dekairelle, Anne-France; Van Marcke, Cédric; Goeminne, Jean-Charles (Frontiers in Oncology, 2023)
A non-small-cell-lung-cancer patient with cerebral metastasis presenting an atypical exon 20 mutation in the EGFR gene had a long-lasting tumor cotrol on mulimodal treatment with osimertinib and stereotaxic radiotherapy on oligoprogressing lesions. Most exon-20 mutations are resistant to first, second and third generation EGFR-directed TKI. This case was discussed on our molecular tumour board. As the more specific exon-20 targeted therapies were not yet available and as sporadic short responses on the third generation EGFR-directed TKI, osimertinib had been described, the patient started osimertinib. She had a prolonged tumoral response on Osimertinib. The patient is still asymptomatic up to 32 months after initiating the medication. This case confirms that not all exon20 EGFR mutations are equal to osimertinib and that the localization of the exon 20 insertion mutation is probably important to consider when treating EGFR mutated NSCLC. The long-term clinical benefit can be maintained through stereotactic radiotherapy on focal progressive lesions.